PENINGKATAN PENGETAHUAN TENTANG BUDIDAYA, KHASIAT DAN MANFAAT LEBAH MADU GALO-GALO GENIOTRIGONA THORACICA DAN HETEROTRIGONA ITAMA BAGI KESEHATAN PADA KELOMPOK TANI TRISULA MUDA KENAGARIAN API-API PASAR BARU KECAMATAN BAYANG KABUPATEN PESISIR SELATAN - Gusni, Jufrika; Miswarti, Miswarti; Eni, Rosmi; Jasmi, Jasmi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Many studies have confirmed the benefits of galo-galo bee honey for health, even BPOM has determined geniotrigona thoracica and heterotrigona itama honey as one type of medicine. In addition, thoracica and itama honey also contain various important minerals such as calcium, magnesium, sodium, copper, manganese, iron, potassium, and phosphorus. In addition, galo-galo bee honey also contains various vitamins, such as vitamins B1, B2, K and C, as well as several enzymes that are good for digestion and can heal wounds. The Trisula Muda Forest Farmer Group is a farmer group initiated by the Kenagarian Api-Api Kecamatan, Bayang Pes-sel District. There are still many problems that are still felt by this farmer group, including group members not knowing how to cultivate, the efficacy and benefits of galo-galo bee honey for health. The target of the Community Partnership Program with partners focuses on increasing the knowledge of farmer group members regarding the cultivation, efficacy and benefits of galo-galo bee honey for health. To achieve this, it is necessary to hold counseling and to the young trisula farmer group. Extension is carried out by bringing in professional experts on the cultivation of Galo-galo bees by assessing the pre and post knowledge of the members of the farmer group. The output targets produced from this Community Partnership Program include: publication through accredited national scientific journals, articles in the mass media, posters, and videos of implementation with a duration of ± 5 minutes Keyword: beekeeping, benefits of honey, Health